The concept of sustainable innovation as applied to banking intermediation - Korenik, Dorota (Koncepcja innowacji zrównoważonej w pośrednictwie bankowym, 2019)
The aim of this paper is to develop a framework for sustainable financial innovation, especially in banking intermediation. The author proceeds in two stages: first, tying the term of sustainable innovation to various paradigms of the role of banks in the economy in order to address that particular innovation clearly to a bank in a way that takes Responsible Research & Innovation (RRI) ideas into account. There has been no such approach to recognizing and interpreting financial innovation and sustainable financial innovation in banking intermediation in the existing theoretical achievements of banking. Secondly, examining the difference between sustainable innovation and incremental innovation. In the conclusion, the author presents the results of compiling three research perspectives (the role of banks, RRI, sustainable innovation versus incremental innovation) into an integrated approach to interpreting the term of sustainable financial innovation in banking intermediation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 63-77
Keywords: financial sustainable innovation; banking intermediation; zrównoważona innowacja finansowa; pośrednictwo bankowe